TEKNOLOGI DAN PEDAGOGI: KAHOOT! DAN QUIZZIZ SEBAGAI MEDIA PEMBELAJARAN DI SEKOLAH DASAR - Tumurang, Hetty J; H Chandra, Franscisca (Proceeding of Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2023)
In welcoming the era of Society 5.0, the Indonesian government has prepared a flexible Kurikulum Merdeka at various levels of education, including in elementary schools. The Kurikulum Merdeka emphasizes project-based learning, focusing on essential mater and flexibility for teachers to explore determining learning methods according to student abilities. In accordance with the concept of Society 5.0 which defines that technology and humans will coexist in order to improve the quality of human life, it is very important for elementary school teachers to utilize technology for learning in accordance with the concepts of the Kurikulum Merdeka and Society 5.0. One aspect of pedagogy in improving the quality of learning is that the ability of such learning to increase student interest and motivation. Information Technology in the form of learning gamification can answer this need. Research has proven that using game-based learning can improve student learning outcomes and motivation. This paper will discuss two learning media based on information technology that use games as a means of learning, namely Kahoot! and Quizzis. Research has proven Kahoot! and Quizizz is able to improve learning outcomes and motivation of elementary school students, especially during the Covid-19 era, where students must take part in online learning. In this paper, we will discuss the technological and pedagogical aspects of the two media.